Elevated physiological arousal is associated with larger but more variable neural responses to small acoustic change in children during a passive auditory attention task - S.V. Wass; K. Daubney; J. Golan; F. Logan; E. Kushnerenko (Developmental Cognitive Neuroscience, 2019)
Little is known of how autonomic arousal relates to neural responsiveness during auditory attention. We presented N = 21 5-7-year-old children with an oddball auditory mismatch paradigm, whilst concurrently measuring heart rate fluctuations. Children with higher mean autonomic arousal, as indexed by higher heart rate (HR) and decreased high-frequency (0.15-0.8 Hz) variability in HR, showed smaller amplitude N250 responses to frequently presented (70%), 500 Hz standard tones. Follow-up analyses showed that the modal evoked response was in fact similar, but accompanied by more large and small amplitude responses and greater variability in peak latency in the high HR group, causing lower averaged responses. Similar patterns were also observed when examining heart rate fluctuations within a testing session, in an analysis that controlled for between-participant differences in mean HR. In addition, we observed larger P150/P3a amplitudes in response to small acoustic contrasts (750 Hz tones) in the high HR group. Responses to large acoustic contrasts (bursts of white noise), however, evoked strong early P3a phase in all children and did not differ by high/low HR. Our findings suggest that elevated physiological arousal may be associated with high variability in auditory ERP responses in young children, along with increased responsiveness to small acoustic changes. Keywords: Auditory attention, Intra-individual variability, Physiological stress